Perbandingan Jenis Media Tanam dengan Sistem Aquaponik Terhadap Pertumbuhan dan Hasil Melon Madu (Cucumis melo L.) - Siregar, Maimunah (UNIVERSITAS LABUHANBATU, 2024)
The aquaponic plant cultivation system is used to utilize narrow urban land in order to increase urban agricultural production. The aim of the research is to determine the effect of comparing types of planting media with an aquaponic system on the growth and yield of honey melon plants (Cucumis melo L.). This research used a non-factorial Complete Randomized Design, with 4 treatment and 5 replication with the factors studied was the comparison of several types of planting media for the